Roberto Mangabeira Unger’s Theory of Empowered Democracy: A Solution to Antinomies of Liberal Democracy? - Kaminskas, Dominykas (Politologija, 2024)
The purpose of this article is to analyze Roberto Mangabeira Unger’s theory of empowered democracy and to evaluate it with regard to antinomies of liberal thought as formulated by the author himself. This article discusses the main presumptions of Unger’s political philosophy and his conceptualization of politics. The theory of empowered democracy is analyzed as an attempt to overcome the antinomy of the universal and the particular, which permeates the liberal worldview. Unger criticizes liberal thought and its central components – liberal psychology and ethics. This critique of liberalism serves as a basis for the philosopher’s vision of politics, at the centre of which is an emancipated and autonomous individual. “Negative capability”, which is the power of individuals to review and rebuild their social contexts, helps them create a political order, which aims to create a “bigger life for all”. To empower individuals, Unger offers a wide-ranging set of changes – starting with more plasticity in political institutions and ending with political protection of the individual ensured by “immunity rights” and prevention of “false necessities”. This article aims to show that Unger’s theory ultimately fails in this goal due to contradictions between the theory of empowered democracy and the author’s own conception of politics as well as due to questionable sustainability of such solution.
Keywords: Roberto Unger; empowered democracy; liberal democracy